2012
DOI: 10.1007/s10508-012-9955-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Consequences of Gender Typicality: The Mediating Role of Communality

Abstract: Considerable work has shown the benefits for psychological health of being gender typed (i.e., perceiving oneself in ways that are consistent with one's sex). Nevertheless, little is known about the reasons for the link. In two studies of young adults (total N = 673), we studied (1) the ways in which gender typing is predicted from gender-related interests and personal qualities, and (2) links between gender typing and adjustment (self-esteem and negative emotionality). In the first study, gender typicality wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Intergroup bias refers to same-gender favoritism. We assessed youth's gender typicality and felt pressure for gender conformity in the present study because these two dimensions focus on evaluations of the self and have been shown to be related to adjustment (DiDonato & Berenbaum, 2013;Egan & Perry, 2001;Jewell & Brown, 2014). 1 Across childhood and adolescence, boys tend to report higher levels of gender typicality and felt pressure for gender conformity than girls (Corby et al, 2007;Egan & Perry, 2001;Hoffman, Dumas et al, 2017;Smith & Leaper, 2006).…”
Section: Gender Typicality and Felt Pressure For Gender Conformitymentioning
confidence: 99%
“…Intergroup bias refers to same-gender favoritism. We assessed youth's gender typicality and felt pressure for gender conformity in the present study because these two dimensions focus on evaluations of the self and have been shown to be related to adjustment (DiDonato & Berenbaum, 2013;Egan & Perry, 2001;Jewell & Brown, 2014). 1 Across childhood and adolescence, boys tend to report higher levels of gender typicality and felt pressure for gender conformity than girls (Corby et al, 2007;Egan & Perry, 2001;Hoffman, Dumas et al, 2017;Smith & Leaper, 2006).…”
Section: Gender Typicality and Felt Pressure For Gender Conformitymentioning
confidence: 99%
“…We chose these constructs because of their established relations to well‐being. Higher levels of gender typicality are associated with lower levels of psychopathology, positive psychosocial adjustment, and greater academic motivation in adolescent and young adult racially/ethnically diverse samples (DiDonato & Berenbaum, ; Jewell & Brown, ; Skinner, Kurtz‐Costes, Wood, & Rowley, ; Smith & Leaper, ; Vantieghem, Vermeersch, & Van Houtte, ). In contrast, higher levels of felt pressure in preadolescents and adolescents are associated with lower levels of psychosocial adjustment (Corby, Hodges, & Perry, ; Yunger, Carver, & Perry, ).…”
Section: Gender Identity Development During Adolescencementioning
confidence: 99%
“…Thus, stereotypical gendered personality characteristics remain entrenched in our world view. Moreover, individuals who define themselves as gender typical show higher levels of psychological well-being than those who do not (DiDonato & Berenbaum, 2013), most likely because individuals who define themselves as gender-typical also value being a member of that category and achieve self-esteem through a sense of belonging and 'being like' others in their group (DiDonato & Berenbaum, 2013;Bigler & Liben, 2007).…”
Section: Gender and Gender Identitymentioning
confidence: 99%